Complement Protein Isoforms in CSF as Possible Biomarkers for Neurodegenerative Disease - Finehout, Erin J.; Franck, Zsofia; Lee, Kelvin H. (Disease markers, 2005)
It has been suggested that the activation of the complement system is involved in the pathogenesis of several neurodegenerative diseases including Alzheimer’s disease (AD), Parkinson’s disease (PD), and multiple sclerosis (MS). Here, the CSF expression levels of complement proteins C3b, C4b, factor B, and factor H were compared between normal subjects and patients diagnosed with AD, PD, MS, and neurosyphilis. The CSF proteins were initially separated using two‐dimensional gel electrophoresis, which allowed the comparison of some of the individual complement isoforms. Patients with AD, PD, and MS all showed more than one complement isoform with a significant change ( p < 0.05) in CSF expression level compared to normal subjects. PD patients were found to have the greatest number of significantly changed isoforms, all showing a decreased expression level in PD CSF. The complement isoforms examined were able to distinguish between some, but not all, of the diseases studied. The data suggest that when investigating a protein as a possible biomarker, it may be useful to compare individual protein isoform expression levels in addition to the more commonly measured total protein expression level.